FINANCING OF INSTITUTIONS OF INNOVATIVE DEVELOPMENT ON THE CONDITIONS OF PUBLIC-PRIVATE PARTNERSHIP - Nataliia O. Riazanova (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
Today, many infrastructure projects aimed at stimulating innovative development of territories are being implemented. Most of these projects are implemented only in partnership with the state and business. The effectiveness of these projects is different, which necessitates the study of the problems of cooperation in the form of public-private partnership (PPP) and increase the efficiency of project management that affect the territorial innovation development. The scientific works of F. Berger, V. Varnavsky, M. Gotre, M. Gerard, E. Zusman, T. Kryshtal, L. Leon, A. Reid, T. Voronkova, E. Savas, P. Savransky, L. Sharinger and other domestic and foreign authors made a significant contribution to solving PPP problems and its use in the innovation sphere. PPP in the innovation sphere is able to improve the mechanisms of interaction between the state and private entrepreneurship throughout the innovation cycle: from research, commercialization of scientific and technical developments and technologies to the production of knowledge-intensive technological products; improving the efficiency of budget financing. The basis for building innovation in Ukraine can be the interaction of the state, science, education and business through the use of PPP. PPP projects are traditionally financed through a combination of financial resources from various sources: private sector funds (including international investors), budgets of all levels, funds of state and joint ventures, credit resources of financial institutions, funds of development institutions. All parties must participate in the distribution of financial benefits from the project, and according to the formula approved before signing the agreement. The general approach in the distribution of profits between the partners is that it should be carried out in accordance with the percentage of investment costs of the parties to the contract under the PPP. The concept of efficiency reflects the relationship between results (management, production, transactions, interactions, etc.) and the costs incurred to achieve them. Interaction conditions associated with project risks that may change over the long-life cycle of projects. PPP has every reason to become one of the strategic directions of development and modernization of infrastructure, industry, energy, innovation, which affects, above all, priority projects aimed at attracting investment from private companies. Forms of financing of institutes of innovative development on the conditions of PPP are defined, possible ways of increase of efficiency of functioning of institutes of innovative development on the conditions of PPP are analyzed. The system of indicators for evaluating the effectiveness of innovative development institutions created on the basis of partnership between the state and business, taking into account the interests of each of the interacting parties, which allows not only to assess the social and economic value of partnership, but also the innovative component of projects.